Dos nuevos generos de anelidos poliquetos para la peninsula iberica: Neopseudocapitella Rullier & Amoureux 1979 y Demonax Kinberg,1867 - Capaccioni-Azzati, R.; Torres-Gavilá & Ten, J. (Thalassas, 1992)
Two Polychaete species, Neopseudocapitella brasiliensis Rullier & Amoureux, 1979 (F. Capitellidae) and Demonax brachychona (Claparede, 1870), are described for the first time for the lberian fauna. Both genera are also new for such fauna. Furthermore, N. brasiliensis wasn't known up to date for the Western Mediterranean basin. Some interesting data about the ecology of both species are included; the validity of the genus Neopseudocapitella, considered by Ewing (1986) as juvenile of other genus, with some ripe specimens collected by us are discussed.
World Polychaeta Database (WPolyDb). Not known to be online, except here